Frequency of Anemia in Patients with Acute Coronary Syndrome - Muhammad Usman, Bader Javed, Arslan Ahmed, Muhammad Muneeb, Zanib Javed Chatha, Afsheen Nigar, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The WHO defines anemia as a condition wherein the hemoglobin level falls below 13 grams per liter in males and 12 grams per liter in females. It is a process that involves supplying the body with oxygen, and it is relevant for the management of acute coronary syndrome. The prevalence of this condition is highly variable globally, and it has been observed in around 10 to 58% of all cases. This study was conducted to evaluate the frequncy of this condition in patients with ACS. Methodology: The research was conducted between December 1, 2020, and May 31, 2021, at the Punjab Institute of Cardiology in Lahore. Men and women between the ages of 30 and 70 who presented with ACS were included in the study. Patients with end-stage liver disease, malignancy, or anemia due to any other cause i.e. aplastic anemia, hemolytic anemia, or anemia of chronic disease were excluded. Detailed clinical and socio-demographic information was collected in age, gender, weight, height, body mass index (BMI), smoking, diabetes mellitus, hypertension, and dyslipidemia recorded on a predesigned proforma. Then 5 ml of venous sample was drawn for each case and their hemoglobin level was assessed by using Certeza HB-101 (Germany) machine and anemia was labeled. Results: Participants' ages from 30 to 70 years old, with the mean age being 55.9. Seventy-two percent of the patients were between the ages of 51 and 70. The gender breakdown of the 76 patients was 58 men (76.32%) and 18 girls (23.68%). Twenty-two individuals (28.95%) were discovered to have anemia with their Acute Coronary Syndrome. Practical Implication: The advice that high-risk individuals with acute coronary syndrome be screened for anemia and treated promptly if they are found to have the condition. Conclusion: This study concluded that there is high frequency of anemia in patients with acute coronary syndrome. Keywords: Acute Coronary Syndrome, Anemia, Mortality, Coronary artery disease,